Systematic review: interactions between aspirin, and other nonsteroidal anti‐inflammatory drugs, and polymorphisms in relation to colorectal cancer. Issue 2 (28th May 2014) - Andersen, V.; Vogel, U.
Summary Background Nonsteroidal anti‐inflammatory drugs (NSAIDs) include aspirin (acetylsalicylic acid, ASA). Long‐term use of NSAIDs has been associated with lowered risk of colorectal cancer (CRC), but the use is hampered by adverse effects. Also, the anti‐carcinogenic effects of NSAIDs are incompletely understood. Understanding biological effects of NSAIDs may help developing new preventive medical strategies. Aim To identify gene–environment interactions between genetic variation and NSAID use in relation to risk of CRC. Methods We performed a PubMed literature search and all studies reporting original data on interactions between NSAIDs and polymorphisms in relation to CRC were evaluated. Results We found indications that aspirin interacted with rs6983267 close to MYC (encoding a transcription factor involved in cell cycle progression, apoptosis and cellular transformation) and NSAIDs interacted with rs3024505 and rs1800872 in or close to IL10 (encoding IL‐10) in preventing CRC. Homozygous carriers of the variant allele of rs6983267 (ca. 25% of the population) halved their risk for CRC by aspirin use compared to homozygous wildtype carriers who did not benefit from aspirin intake. No interaction between use of NSAIDs and PTGS‐2 (encoding COX‐2) in relation to CRC risk was detected. Other findings of interactions between genes in inflammatory and oncogenic pathways and NSAIDs were considered suggestive. Conclusions Knowledge of underlying biological effects of NSAIDs in relation to CRC is scarce and the basis for stratifying the patients for preventive treatment is not yet available. Further studies assessing interactions between long‐term NSAID exposure and genetic variation in relation to CRC are warranted in large well‐characterised prospective cohorts.